Risk Factors for Early Childood Caries: A cross-sectional study in a Dental School - KARGÜL, BETÜL (AVES, 2018)
Objective: This study aimed to investigate possible early childhood caries (ECC) risk indicators in preschoolers who applied for examination/treatment at the Government University Pediatric Dentistry Clinic, Istanbul, Turkey. Material and Methods: Children aged 36-71 months and their mothers who applied for examination/treatment and consented were enrolled in this cross-sectional survey during a 3-month period. Mother-child pairs were examined intraorally, and caries experience was recorded using (dmft/DMFT) an index. A structured questionnaire inquiring oral hygiene habits and diet history of the children was employed to interview the mothers. Categorical data from children with no clinical caries (NC), ECC, Severe ECC (S-ECC) were compared using Chi-square test and correlation of caries experience in mother-child pairs and were tested with Spearman rho. Statistical significance was set p<0.05. Results: Two hundred sixty-six children (4.41 +/- 0.87 years old) were enrolled in the study. Forty (15.04%) children were diagnosed with ECC, 209 with S-ECC and 17 had NC. Breastfeeding was practiced by 255 (96.2%) mothers, but the duration was not different among groups. There was no significant association with breastfeeding beyond 24 months and caries (p=0.743). Children with S-ECC were snacking more frequently with sweets than ECC (p=0.012). The number of mothers with a visible dental plaque was higher in S-ECC than ECC (p<0.01). Maternal DMF-T scores significantly correlated with their children's dmf-t in the whole sample (r=0.547, p<0.01). Conclusion: Preventive measures should begin from pregnancy and focus on oral health/hygiene education to mothers to avoid the devastating effects of ECC.
Keywords: Dental Caries; breastfeeding; bottle feeds; oral health; EARLY-CHILDHOOD CARIES; PRESCHOOL-CHILDREN; ORAL HYGIENE; ASSOCIATION; DEFINITION; PREVALENCE; TURKEY; INDIA; OLD